Pengenalan Angka Dalam Bahasa Arab Dan Bahasa Inggris Menggunakan Media Gambar Pada TK/TPA Al-Hakam Palangka Raya - Mega Selfia; Meli Yuli Yanti; Hadma Yuliani; Zaitun Qamariah (Pakis Journal Institute, 2024)
The introduction of numbers in Arabic and English through pictures and singing at TK/ TPΑ Al- Hakam Palangka Raya is an activity that is quite popular with children. This devotion aims to ensure that children can recognize numbers in Arabic and find out the effectiveness of teaching methods using picture media and the addition of singing methods. The service method is carried out using direct or offline communication through a direct approach to children, which is held in 1 meeting. The objects of this service are class 1A children at Al- Hakam Kindergarten/ TPA Palangka Raya. The tools and materials used in this research are image media. The results of this service show that the image media and singing method are very effective in developing knowledge of recognizing Arabic and English numbers in early childhood in class 1A. The children seemed to pay good attention and were enthusiastic about following the teaching of number recognition during class, the children also seemed to be united in pronouncing the numbers in Arabic and English well.